ChemInform Abstract: A Closer Look at the Bromine—Lithium Exchange with tert‐Butyllithium in an Aryl Sulfonamide Synthesis. Issue 46 (24th October 2013) - Waldmann, Christopher; Schober, Otmar; Haufe, Guenter; Kopka, Klaus
Abstract Various heteroaryl sulfonamides are prepared by a one‐pot four‐step procedure including bromine‐lithium exchange of heteroaryl bromides.